2009
DOI: 10.1128/jcm.02392-08
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Syphilis in Patients in Canada: Azithromycin Resistance and Detection of Treponema pallidum DNA in Whole-Blood Samples versus Ulcerative Swabs

Abstract: Although detection of Treponema pallidum DNA in whole-blood specimens of syphilis patients has been reported, it is uncertain at what stage of the disease such specimens are most suitable for the molecular diagnosis of syphilis. Also, few studies have directly compared the different gene targets for routine laboratory diagnostic usage in PCR assays. We examined 87 specimens from 68 patients attending two urban sexually transmitted disease clinics in Alberta, Canada. PCR was used to amplify the T. pallidum tpp4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 30 publications
4
59
0
5
Order By: Relevance
“…These findings are consistent with those of previous studies reporting a sensitivity of 80.39% and a specificity of 98.4%, which were based on positive PCR results for 55 patients (26). Moreover, for a total population of 68 patients, a detection sensitivity of 75% has been reported for swab samples from patients with primary syphilis (29). In a recent study of 716 individuals, including 114 patients diagnosed with primary syphilis, the sensitivity was 72.8% and the specificity was 95.5% (17).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are consistent with those of previous studies reporting a sensitivity of 80.39% and a specificity of 98.4%, which were based on positive PCR results for 55 patients (26). Moreover, for a total population of 68 patients, a detection sensitivity of 75% has been reported for swab samples from patients with primary syphilis (29). In a recent study of 716 individuals, including 114 patients diagnosed with primary syphilis, the sensitivity was 72.8% and the specificity was 95.5% (17).…”
Section: Discussionsupporting
confidence: 82%
“…New detection strategies have been developed during the last 15 years that are based on advances in our knowledge of the sequence of the T. pallidum genome (13 (2,3,6,15,17,18,23,30,31,32,34,39), and others, such as polA, being involved in genome duplication (9,27,28,35). Recent comparisons of the results for the detection of T. pallidum DNA obtained by the amplification of the tpp47, bmp, polA, and 23S rRNA genes showed that these tests give concordant results (29).…”
mentioning
confidence: 99%
“…Recently, a second point mutation (A2059G) in the same gene was also found to be associated with macrolide treatment failure in syphilis patients (10). Azithromycin treatment failures have been reported in Canada, Europe, Asia, and the United States (7,8,(10)(11)(12)(13)(14)(15). The percentages of T. pallidum-positive clinical specimens containing the A2058G mutation have increased significantly over time in San Francisco and Seattle, from 4 and 9% in 2002 to 77 and 56% in 2005, respectively (8,(16)(17)(18).…”
Section: Detection Of the A2058g And A2059g 23s Rrna Gene Point Mutatmentioning
confidence: 99%
“…Martin at al used PCR to amplify the three T. pallidum genes: tpp47 bmp (Noordhoek et al, 1991) and polA . PCR was positive in 36%(19/53) specimens, three treponemal gene PCR assays gave concordant results in all specimens collected from syphilis patients, regardless of the specimen types (blood or swab) or the stages of disease (primary or secondary) (Martin et al, 2009). Another study found positivity ratio of 39.1% for ttp47 PCR (260 bp) and 31.1% for polA PCR (378 bp), in blood samples from patients with latent syphilis (Castro et al, 2007).…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%